2018
DOI: 10.3750/aiep/02295
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on age, growth and reproduction of Mustelus mustelus (Elasmobranchii: Carcharhiniformes: Triakidae) inhabiting the Gulf of Iskenderun, north-eastern Mediterranean Sea

Abstract: Ozcan E.I., Başusta N. 2018. Preliminary study on age, growth and reproduction of Mustelus mustelus (Elasmobranchii: Carcharhiniformes: Triakidae) inhabiting the Gulf of Iskenderun, north-eastern Mediterranean Sea. Acta Ichthyol. Piscat. 48 (1): 27-36.Background. Shark populations within the eastern Mediterranean are declining due to overfishing. Unfortunately, our knowledge on the biology of sharks and specifically dogfishes within eastern Mediterranean is extremely limited due to the lack of landings. Mustel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In both species, the L 50 values reported were smaller in the Gulf of Gabès ( M. mustelus : males: 97.1 cm, females: 117.2 cm, Saïdi et al ., ; M. punctulatus : males: 81.4 cm, females: 95.6 cm, Saïdi et al ., ) than those in the northern Adriatic Sea. Similar results were obtained for M. mustelus in the Gulf of Iskenderun in Turkey ( L 50 of the males: 92 cm, L 50 of the females: 109 cm; Ozcan & Başusta, ). This result is in line with a latitudinal pattern of maximum size and size at sexual maturity observed in the Mediterranean Sea in the small‐spotted catshark Scyliorhinus canicula L 1758 (Finotto et al ., ) and, among the few other sharks for which data are available, in the starspotted smooth‐hound Mustelus manazo Bleeker 1855 in the Pacific Ocean (Yamaguchi et al ., ).…”
Section: Mustelus Mustelus and Mustelus Punctulatus: Estimates Of Lifsupporting
confidence: 82%
See 1 more Smart Citation
“…In both species, the L 50 values reported were smaller in the Gulf of Gabès ( M. mustelus : males: 97.1 cm, females: 117.2 cm, Saïdi et al ., ; M. punctulatus : males: 81.4 cm, females: 95.6 cm, Saïdi et al ., ) than those in the northern Adriatic Sea. Similar results were obtained for M. mustelus in the Gulf of Iskenderun in Turkey ( L 50 of the males: 92 cm, L 50 of the females: 109 cm; Ozcan & Başusta, ). This result is in line with a latitudinal pattern of maximum size and size at sexual maturity observed in the Mediterranean Sea in the small‐spotted catshark Scyliorhinus canicula L 1758 (Finotto et al ., ) and, among the few other sharks for which data are available, in the starspotted smooth‐hound Mustelus manazo Bleeker 1855 in the Pacific Ocean (Yamaguchi et al ., ).…”
Section: Mustelus Mustelus and Mustelus Punctulatus: Estimates Of Lifsupporting
confidence: 82%
“…Indeed, the former present a larger maximum size and size at maturity than the latter. Data on maximum age and age at maturity are available only for M. mustelus (Ozcan & Başusta, ). Larger maximum sizes and sizes at maturity may be related to higher maximum age and age at maturity; nonetheless, the lack of data for M. punctulatus does not allow comparisons of maximum age, growth rate and age at maturity between the species.…”
Section: Mustelus Mustelus and Mustelus Punctulatus: Estimates Of Lifmentioning
confidence: 99%
“…When the t-test results was used for the significance condition of the regression coefficients, it was identified that length data could be used in highly reliable to estimate weight (Özcan and Başusta, 2018). Condition factor was calculated for sexes (Table 2) and all age-groups.…”
Section: Resultsmentioning
confidence: 99%
“…The regression analysis has shown that fish length had a highly significant correlation with weight (P < 0.001). The t-test results indicated that length data could be used to estimate weight in high reliability (Ozcan and Başusta 2018). Condition factor.…”
Section: Discussionmentioning
confidence: 96%